Predictive Markers of Bronchial Hyperreactivity in a Large Cohort of Young Adults With Cough Variant Asthma - Malerba, Mario; Ragnoli, Beatrice; Azzolina, Danila; Montuschi, Paolo; Radaeli, Alessandro (Frontiers in Pharmacology, 2021)
Cough variant asthma (CVA), a common asthma phenotype characterized by nonproductive cough and bronchial hyperreactivity (BHR), is usually detected by bronchial provocation tests (BPTs) which are time-consuming, expensive, and unsafe. The primary study objective was to provide proof of concept for the use of fractional exhaled nitric oxide (FENO), eosinophil count percentage in induced sputum (sEOS%), forced expiratory flow between 25 and 75% of forced vital capacity (FEF25–75%) % predicted value, and FEF25–75% z-scores as surrogate markers predicting BHR in young adults with suspected CVA; the secondary objective was to compare the diagnostic performance of the various techniques. Three hundred and ten subjects (median age 24 years) were included in a cross-sectional study. Subjects were characterized as BHR positive (POS) (n = 147) or BHR negative (NEG) (n = 163) according to methacholine BPT. Classification accuracies were expressed as areas under the receiver operator characteristic curves (AUC). Compared with BHR NEG, FEF25–75% % predicted value and FEF25–75% z-scores were lower in the BHR POS group (p < 0.001), whereas FENO (p < 0.001) and sEOS% were higher (p < 0.001). AUC values for detecting BHR were as follows: FENO, 0.98 (SD = 0.02); sEOS%, 0.98 (SD = 0.02); FEF25–75% % pred, 0.93 (SD = 0.05); FEF25–75% z scores, 0.92 (SD = 0.05). Optimal cutoff values (OCV) for BHR prediction were as follows: FENO, 32.7 ppb (sensitivity = 0.93, specificity = 0.96), sEOS%, 3.80% (sensitivity = 0.94, specificity = 0.94), FEF25–75% % predicted value, 80.0% (sensitivity = 0.90, specificity = 0.87), and FEF25–75% z-score, −0.87 (sensitivity = 0.89, specificity = 0.87). Non-invasive/semi-invasive airway inflammatory or small airway functional measures might be used as surrogate markers predicting BHR in young adults with suspected CVA.